2016
DOI: 10.1039/c6cp04933h
|View full text |Cite
|
Sign up to set email alerts
|

XPS enables visualization of electrode potential screening in an ionic liquid medium with temporal- and lateral-resolution

Abstract: We present an X-ray photoelectron spectroscopic (XPS) investigation of potential screening across two gold electrodes fabricated on a porous polymer surface which is impregnated with the ionic liquid (IL) N-N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide [DEME-TFSI]. The IL provides a sheet of conducting layers to the insulating polymer film, and allows monitoring charging and screening dynamics at the polymer + IL/vacuum interface in a laterally resolved fashion across the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 59 publications
4
66
0
Order By: Relevance
“…In particular, the spectroscopic investigation using UHV-based surface science methods still is at its infancy due to a number of experimental challenges. Licence et al, 66,83 133 and Suzer et al 78 We envisage that combining more advanced electrochemical cells with real-time in situ XPS under electrochemical condition will become an important field in the future.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, the spectroscopic investigation using UHV-based surface science methods still is at its infancy due to a number of experimental challenges. Licence et al, 66,83 133 and Suzer et al 78 We envisage that combining more advanced electrochemical cells with real-time in situ XPS under electrochemical condition will become an important field in the future.…”
Section: Discussionmentioning
confidence: 96%
“…[67][68][69][70][71][72] We also exclude studies where the reaction was not carried out in situ, that is, spectra were not recorded while the reaction proceeded, or the sample was moved to a different site in the XPS setup or was even removed from the XPS setup in order to carry out the reaction. [73][74][75][76][77] We also do not address studies that incorporate electrochemical sample manipulation, 66,67,[69][70][71][78][79][80][81][82][83][84][85][86] electrodeposition of metal or organic layers from ILs, [87][88][89][90][91] and IL decomposition 84,[92][93][94][95][96][97][98][99][100][101][102] or nanoparticle formation in ILs. 62,75,103 Each of these topics was studied extensively and would justify a separate review.…”
Section: Introductionmentioning
confidence: 99%
“…The structure factors and the radial distribution functions can be obtained from diffraction patterns as a fingerprint of the ionic liquid. This method is especially useful when thin film is intercalated with ionic liquid materials [93].…”
Section: Basic Analysis Types Of Ils For the Characterization Are Lismentioning
confidence: 99%
“…Several low‐temperature scanning tunneling microscopy studies on in‐plane ordering have also been reported for a low coverage of ionic liquids deposited on gold and silver surfaces . Notably, time‐ and spatially resolved information on potential screening of ionic liquids due to their unique EDL between two electrodes was shown to be attainable using X‐ray photoemission spectroscopy . That experiment provided remarkably clear evidence of long‐range effects of EDL formation through a raster scanning of an X‐ray beam across electrodes when pulses with magnitude of 5 V were applied.…”
mentioning
confidence: 92%